Catalytical nano-immunocomplexes for remote-controlled sono-metabolic checkpoint trimodal cancer therapy - Zhang, Chi (2023)
Checkpoint immunotherapies have been combined with other therapeutic modalities to increase patient response rate and improve therapeutic outcome, which however exacerbates immune-related adverse events and requires to be carefully implemented in a narrowed therapeutic window. Strategies for precisely controlled combinational cancer immunotherapy can tackle this issue but remain lacking. We herein report a catalytical nano-immunocomplex for precise and persistent sono-metabolic checkpoint trimodal cancer therapy, whose full activities are only triggered by sono-irradiation in tumor microenvironment (TME). This nano-immunocomplex comprises three FDA-approved components, wherein checkpoint blockade inhibitor (anti-programmed death-ligand 1 antibody), immunometabolic reprogramming enzyme (adenosine deaminase, ADA), and sonosensitizer (hematoporphyrin) are covalently immobilized into one entity via acid-cleavable and singlet oxygen-activatable linkers. Thus, the activities of the nano-immunocomplex are initially silenced, and only under sono-irradiation in the acidic TME, the sonodynamic, checkpoint blockade, and immunometabolic reprogramming activities are remotely awakened. Due to the enzymatic conversion of adenosine to inosine by ADA, the nano-immunocomplex can reduce levels of intratumoral adenosine and inhibit A2A/A2B adenosine receptors-adenosinergic signaling, leading to efficient activation of immune effector cells and inhibition of immune suppressor cells in vivo. Thus, this study presents a generic and translatable nanoplatform towards precision combinational cancer immunotherapy.